Perspectives on Everyday Life A Cross Disciplinary Cultural Analysis - Berger, Arthur Asa (Springer International Publishing, 2018)
Perspectives on Everyday Life: A Cross Disciplinary Cultural Analysis makes the argument for studying everyday life through a combination of introductory theoretical approaches and a grouping of applications to specific aspects of American culture. The first part of the book addresses the idea of everyday life as considered by distinguished thinkers who have written books about everyday life, such as Sigmund Freud, Fernand Braudel, Henri Lefebvre, Michel de Certeau, and others. The second part of the book uses theories dealt with in the first part of the book to explore objects-such as suitcases, alarm clocks, milk, pacifiers, pressure cookers, smart speakers, and super-glue-and their part in the various rituals of everyday life in America, revealing their hidden meanings.